Analogy, Concept and Cognition - (Mitinunwong) Sirichan, Kanit (Journal of Letters, 2023)
This research paper aims to study analogy as a type of comparative thinking and to investigate whether it is justified to claim that an analogical thought has cognitive content. Two theories in cognitive science claim that an analogy has cognitive content. The first one is called the weak view of analogy in cognition; this is expressed in, for example, the works of Gust et al. (2008), Lakoff & Johnson (1980), Hesse (1966), and Black (1955). The second one is called the strong view of analogy in cognition, seen, for example, in the works of Hofstadter (2001, 2006) and Hofstadter and Sanders (2013). According to the weak view, analogical thought is only a necessary condition of cognition. But in the strong view, analogy is both a necessary and a sufficient condition of cognition. Regardless of the differences, neither theory is justified in claiming analogical content. While the weak view cannot provide an account of the perceptual aspect of content, the strong view suffers from a lack of normative constraint for analogical content.